2022
DOI: 10.1108/ejtd-07-2021-0114
|View full text |Cite
|
Sign up to set email alerts
|

Manager-as-coach and use of scenistic tools for instruction

Abstract: Purpose The purpose of this essay is the provision of a conceptual approach for a manager-as-coach to use for instructional purposes with an employee. Using scenistic materials (cases, incidents, stories), the aim of the essay is to assist the practitioner apply a practical and relatively adaptable instructional approach. While it is intended for application with a single employee, the approach, with modifications, may be used in a small group environment. Design/methodology/approach The methodology was dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The importance of training in organizations in general and for managers, in particular, is very high (Lyons & Bandura, 2022; Milner et al, 2020). Milner et al (2018) suggested that coaching training for managers should be tailored to specific contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of training in organizations in general and for managers, in particular, is very high (Lyons & Bandura, 2022; Milner et al, 2020). Milner et al (2018) suggested that coaching training for managers should be tailored to specific contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies that have explored the relationships between managers who serve as coaches and their subordinates (Adele et al, 2022; Carrell et al, 2021; Kim & Kuo, 2015; McCarthy & Milner, 2013; Milner et al, 2018) point to the positive value of the MAC process (Adele et al, 2022) in improving learning outcomes (Lyons & Bandura, 2022), helping managers adjust their organizational culture to the MAC process (Milner et al, 2020), and enhancing employee performance and work attitudes (Kim et al, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%